Aqueous Lithium Carboxymethyl Cellulose and Polyacrylic Acid/Acrylate Copolymer Composite Binder for the LiNi0.5Mn0.3Co0.2O2 Cathode of Lithium-Ion Batteries. Issue 1 (1st January 2022) - Cui, Yan; Chen, Jiahui; Zhao, Jingyang; Ma, Zhen; Tan, Yuming; Xue, Jianjun; Xu, Hanliang; Nan, Junmin
Abstract : Water-soluble green cathode binders are developed to increase the performance of 18650 type LiNi0.5 Mn0.3 Co0.2 O2 (NMC532) lithium-ion batteries (LIBs). Using four basal substances to prepare the composite binders, it is indicated that the cathode with lithium carboxymethyl cellulose (CMCLi)-polyacrylic acid/acrylate copolymer (type 306 F) composite binder (Marked as Binder C) avoids the corrosion of aluminum substrate, and exhibits stronger adhesive force and better electrolyte adsorption capacity compared to other cathodes with PVDF binder and single aqueous binders. In particular, the electrochemical performance of the batteries with Binder C is also improved, initial specific capacity of 161.5 mAh g −1 at 0.2C and retention capacity of 88.9% at 1C after 1200 cycles are obtained. The batteries with Binder C also exhibit enhanced high-temperature storage performance, there is 97.9% residual capacity when the fully charged batteries are stored in 60 °C for 14 d. The enhanced performance is mainly attributed to the chemical stability and bonding ability of polyacrylic acid/acrylate copolymer and better conduction at the liquid-solid interface caused by CMCLi. These results indicate that Binder C has promising application prospects in the NMC532 cathode, and also provide a reference for the green production of NMC-based LIBs.